Determinants of service quality and perceived value and its impact on customer satisfaction and customer loyalty: an empirical perspective on public transportation sector / Che Anizaliana Che Pei - Che Pei, Che Anizaliana (2011)
Public transport users tend to be dissatisfied when they experience poor service quality provided by public transport. Although there is high demand for public transport, understanding customer needs and how they feel about the services is critical for customer retention as service quality is the important factor that encourages the use of public transport and its services. This study examines the preferred public transport mode in seven different urban areas in the Klang Valley namely, Klang, Shah Alam, Petaling Jaya, Subang Jaya, Kuala Lumpur, Gombak, Ampang and Senawang. Besides that, this study also identifies the seven important elements of public transport services including fares, accessibility, reliability, customer services, communication, trip experience and safety. The aim of this study is to gauge the relationship between service quality, perceived value, customer satisfaction and customer loyalty of existing public transport services. A total of 500 questionnaires were collected and 467 were returned. Descriptive statistics, Cronbach's Alpha and Structural Equation Modelling (SEM) methods have been used to analyze the data. Findings from the descriptive study indicated that LRT is the preferred mode in Klang Valley, while safety is the main important element in public transport services. Results from SEM found support for the effect of the perceived value and satisfaction, perceived value and service quality, perceived value and loyalty; satisfaction and loyalty. However, contrary to results of previous research, service quality had no impact on the satisfaction and loyalty of users. The current research contributes to knowledge in the field of urban transport research. It suggests that better service quality of public transport service is vital to encourage use public transport.